Cross-sectional study of Hepatitis B Awareness among Chinese and Southeast Asian Canadians in the Vancouver-Richmond community. (1st April 2005) - Cheung, Justin; Lee, Tim K; Teh, Chong-Ze; Wang, Caroline YM; Kwan, WC Peter; Yoshida, Eric M
Abstract : BACKGROUND: Hepatitis B (HBV) is endemic and a leading cause of morbidity and mortality in Asia. British Columbia has the highest proportion of Chinese and Southeast Asians among all Canadian provinces. The present study was designed to evaluate the degree of concern for and knowledge of HBV in this high-risk community. OBJECTIVE: Unselected patrons of two large Asian commercial centres in Richmond, British Columbia were surveyed. The variables studied were population demographics, concern for HBV, level of HBV knowledge and awareness of HBV-related cirrhosis or hepatocellular carcinoma (HCC). Associations were assessed using c 2 testing and multiple logistic regression analysis. RESULTS: A total of 1008 individuals participated in the survey. Fifteen incomplete surveys were excluded. Only 7.7% felt that HBV was not a concern for the community. Only 13% of respondents felt that HBV education was adequate in the community. The main sources of community health education were their doctor's office (56.3%) and media (49.1%). A high number stated they were 'aware' of HBV (68%) but over 60% were unaware that HBV could cause HCC or cirrhosis and only 61.3% scored a 'reasonable' level of HBV knowledge. Higher HBV knowledge was significantly associated with increasing age ( P<0.001), higher education ( P<0.001) and the use of media for health education ( P<0.001). Awareness that HBV may cause HCC and cirrhosis was significantly associated with age ( P<0.001), education (P=0.006) and birthplace (P=0.001). INTERPRETATION: HBV education is necessary in this local Asian community. Programs should target younger, less educated adults and elaborate on the potential serious health consequences of HBV. Vehicles for public education should include the physicians' offices and local media.